Tributação e inovação na indústria de petróleo e gás natural do Brasil: uma caracterização do processo de P&D e avaliação setorial da política nacional de incentivos - Leite, Luís Alberto Melchíades (2008)
Taking Petrobras as a representative company in the Brazilian oil and gas sector, this work is addressed to characterize its R&D process, through qualitative and quantitative parameters, reinforcing the importance of technology as a production factor. It also attempts to assess the main impacts of the national innovation policy, including fiscal incentives and other legal mechanisms, on the amount of R&D investments by the sector in recent years. From this perspective, a measure of R&D cost sensitivity and an assessment of fiscal incentives generosity for R&D initiatives in Brazilian oil and gas sector were accomplished.